Sericin Composition in the Silk of Antheraea yamamai - Zurovec, Michal; Yonemura, Naoyuki; Kludkiewicz, Barbara; Sehnal, František; Kodrik, Dalibor; Vieira, Ligia Cota; Kucerova, Lucie; Strnad, Hynek; Konik, Peter; Sehadova, Hana (Biomacromolecules, 2016)
The silks produced by caterpillars consist of fibroin proteins that form two core filaments, and sericin proteins that seal filaments into a fiber and conglutinate fibers in the cocoon. Sericin genes are well-known in Bombyx mori (Bombycidae) but have received little attention in other insects. This paper shows that Antheraea yamamai (Saturniidae) contains five sericin genes very different from the three sericin genes of B. mori. In spite of differences, all known sericins are characterized by short exons 1 and 2 (out of 3-12 exons), expression in the middle silk gland section, presence of repeats with high contents of Ser and charged amino acid residues, and secretion as a sticky silk component soluble in hot water. The B. mori sericins represent tentative phylogenetic lineages (I) BmSer1 and orthologs in Saturniidae, (II) BmSer2, and (III) BmSer3 and related sericins of Saturniidae and of the pyralid Galleria mellonella. The lineage (IV) seems to be limited to Saturniidae. Concerted evolution of the sericin genes was apparently associated with gene amplifications as well as gene loses. Differences in the silk fiber morphology indicate that the cocktail of sericins linking the filaments and coating the fiber is modified during spinning. Silks are composite biomaterials of conserved function in spite of great diversity of their composition.
Keywords: sericiny; Moths; hmyzí proteiny; Amino Acid Sequence; Animals; Sequence Homology, Amino Acid; sekvenční homologie aminokyselin; Phylogeny; hedvábí; Silk; zvířata; fylogeneze; Insect Proteins; Sericins; můry; sekvence aminokyselin